Youth Experience of Trying to Get off the Street: What has Helped and Hindered - Brown, Tracy L.; Amundson, Norman E. (Canadian Journal of Counselling and Psychotherapy, 2010)
This qualitative study involved 20 youth (18 male, 1 female, 1 transgender, ages 19–24) living in Vancouver, British Columbia, who reported 259 critical incidents of what helped or hindered their experiences as they tried to get off the street. What helped included (a) taking responsibility, (b) engaging in constructive activities, (c) friends and family sup-port, (d) changing drug and alcohol use, (e) support from professional organizations, (f) disillusionment with street life, (g) dreams and hope for a different future, (h) income assistance, and (i) leaving negative influences behind. What hindered included (a) drugs and alcohol; (b) emotional struggles; (c) lack of support; (d) enjoyment of homelessness; (e) limited formal education, life skills, and employment; and (f) income assistance dif-ficulties. The results are discussed in relation to implications and recommendations for practice, limitations, and future research.